2006
DOI: 10.1002/bip.20508
|View full text |Cite
|
Sign up to set email alerts
|

A minimalistic 3D pharmacophore model for cyclopentapeptide CXCR4 antagonists

Abstract: Because of its involvement in HIV entry, the chemokine receptor CXCR4 is an attractive target for antiretroviral drugs. Despite the large number of CXCR4 inhibitors studied, the 3D pharmacophore for binding to CXCR4 remains elusive, mainly as a result of conformational flexibility inherent in the identified ligands. In the present study, an exhaustive systematic exploration of the conformational space for a series of analogs of FC131, a cyclopentapeptide CXCR4 antagonist, has been performed. By comparing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
6
24
0
Order By: Relevance
“…Based on an extensive exploration of the conformational space for a series of reported cyclopentapeptide CXCR4 antagonists, Våbenø et al have proposed a minimalistic 3D pharmacophore model for this compound class [101]. The identified features included the spatial arrangement of the pharmacophoric side chains as well as the optimal conformation of the cyclopentapeptide backbone, which was consistent with the experimental solution structure for FC131 [49].…”
Section: Pharmacophore Modelmentioning
confidence: 68%
See 1 more Smart Citation
“…Based on an extensive exploration of the conformational space for a series of reported cyclopentapeptide CXCR4 antagonists, Våbenø et al have proposed a minimalistic 3D pharmacophore model for this compound class [101]. The identified features included the spatial arrangement of the pharmacophoric side chains as well as the optimal conformation of the cyclopentapeptide backbone, which was consistent with the experimental solution structure for FC131 [49].…”
Section: Pharmacophore Modelmentioning
confidence: 68%
“…No further investigation into this scaffold has been published to date. considered as a tripeptidomimetic [101]. In the original study, KRH--1636 was found to be duodenally absorbable and was considered as a promising lead.…”
Section: Tetrapeptidomimetics Cluzeau Et Al Have Reported a Series Ofmentioning
confidence: 99%
“…In an extensive study from 2006, 11 derivatives of FC131, which were believed to share a common binding mode, were docked to a threedimensional model of the transmembrane region of CXCR4 [ 38 ] . The authors had previously published a minimalistic 3D pharmacophore model for cyclopentapeptides suggesting the spatial arrangement of the domains required for CXCR4 binding [ 39 ] , and the ligands were docked according to this model to further elucidate the atomic details of the CXCR4 interaction.…”
Section: T22 T140 and Derivativesmentioning
confidence: 99%
“…This material was prepared by guanidinylation of glycine methyl ester hydrochloride (18) using N,N-di-Boc-1H-pyrazole-1-carboxamidine followed by hydrolysis of the methyl ester of the resulting 19…”
Section: Scheme 4 Scaffold and Retrosynthetic Strategymentioning
confidence: 99%